Yoruba Contemporary Gele: A Stylistic Appraisal - Akinde, Toyin; Tijani, Aminat O.; Akintonde, Moses A.; Eyinade, Adedapo S. (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Gele, pronounced gay-lay, is simply head covering, typified and rooted in feminine fashion of the Yoruba, home and abroad. It is the ultimate apparel adorned by the female folks of all age, class and status; giving acclaimed quintessential top notch appeal, deserving of a true Yoruba dress. In other words, clothing accessories conglomerating costume, footwear, makeup and hairstyle is incongruous without gele particularly in the Yoruba milieu. Gele congruity in female dressing is unequivocably material to recent proclivity and self expressions as observed in generation and regenerations of well over thirty stylish gele ideas and innovations. In view of the latter, this paper examines gele stylistic inclination; using Ibadan as its case in point, being the largest city state in modern Yoruba history. The methodology adopted was triangular approaches of participatory field investigation, online survey and artistic visualisation. Gele adherents and stylists of Ibadan metropolis were physically interviewed, figures sourced virtually and appraised artistically. Eight gele styles were shortlisted and stylistically visualised. Findings revealed dynamism in prevailing gele styles, with apparent classic and comely finesse on beholders. Consequently, this paper hopes it finding will help promotes gele styling among teeming youths locally and globally; provoking studies on the subject matter.